The emergence of common health conditions across the life course: evidence from the Born in Bradford family cohort [version 2; peer review: 2 approved] - John Wright; Gillian Santorelli; Rosemary R.C. McEachan; Krishnarajah Nirantharakumar; Dan Lewer; Katherine Phillips; Siang Ing Lee (Wellcome Open Research)
Background Born in Bradford (BiB) is a family cohort study with linked routine health records. We calculated the rates of common health conditions and explored differences between White European and South Asian participants. Methods 21 health conditions were identified using diagnostic codes and prescription records extracted from electronic health records. We calculated 2-year period prevalence before recruitment and incidence rates per 1000 person-years were calculated from recruitment to the end of 2021 (or censoring). Age-adjusted Cox proportional hazard models estimated hazard ratios (HR) by ethnicity. Results The sample included 9,784 mothers, 52% were of South Asian heritage and 48% were White European. The highest prevalence and incidence rates were observed for common mental health disorders and eczema. South Asian women had higher incidence of 14 conditions, including diabetes (HR 3.94 [95% CI 3.15, 4.94]), chronic liver disease (2.98 [2.29, 3.88]) and thyroid disorders (1.87 [1.50, 2.33]), but lower incidence of cancer (0.51 [0.38, 0.68]), other and common mental health disorders (0.56 [0.45, 0.71] and 0.69 [0.64, 0.74] respectively), and other neuromuscular conditions (0.63 [0.49, 0.82]). Conclusions/discussion This study reveals significant differences in the occurrence of several non-communicable health conditions between White European and South Asian women. The observed higher incidence of several conditions in South Asian women, consistent with established knowledge regarding elevated risks for diseases such as diabetes, likely reflects the complex interplay of social, cultural, lifestyle, environmental, and genetic determinants. These findings emphasise the need for culturally sensitive and targeted public health interventions aimed at addressing modifiable risk factors at both the individual and systemic levels to alleviate the burden of long-term health conditions and reduce existing health inequalities.